The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/scan/nsy063
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of sibling closeness and association with externalizing behavior in adolescence

Abstract: Sibling relationships have been linked to adolescent externalizing behaviors, but the neurobiological factors that underlie this association have not been identified. This study investigated sibling closeness and birth order as a predictor of adolescent externalizing behavior via differences in neural processes during safe decision-making. A total of 77 adolescents (range = 12–15 years, Mage = 13.45 years, 40 females) completed a computerized driving task during a functional MRI scan. Results showed that adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…While many theories have been proposed to describe neurobiological sensitivity to social context (Schriber & Guyer, 2016), no empirical study to date has implemented fMRI to identify changes in the brain as a result of social learning from salient social models during risk taking, despite the evidence suggesting the pivotal role social learning plays in adolescent decision making (see Telzer, van Hoorn, Rogers, & Do, 2018). Nonetheless, emerging research has begun to highlight how peers (Chein et al, 2011; Telzer, Ichien, & Qu, 2015; Telzer, Miernicki, et al, 2018; van Hoorn, McCormick, Rogers, Ivory, & Telzer, 2018; Vorobyev et al, 2015), parents (Guassi Moreira & Telzer, 2018; Qu et al, 2016, 2015; Telzer, Ichien, et al, 2015; Telzer, Fuligni, et al, 2015; van Hoorn et al, 2018), and even siblings (Rogers, McCormick, van Hoorn, Ivory, & Telzer, 2018) influence adolescent neurodevelopment and risk taking (for a meta‐analysis, see van Hoorn, Shablack, Lindquist, & Telzer, 2019). These studies highlight a set of neural candidates to examine as promising indices of adolescent susceptibility to social influence.…”
mentioning
confidence: 99%
“…While many theories have been proposed to describe neurobiological sensitivity to social context (Schriber & Guyer, 2016), no empirical study to date has implemented fMRI to identify changes in the brain as a result of social learning from salient social models during risk taking, despite the evidence suggesting the pivotal role social learning plays in adolescent decision making (see Telzer, van Hoorn, Rogers, & Do, 2018). Nonetheless, emerging research has begun to highlight how peers (Chein et al, 2011; Telzer, Ichien, & Qu, 2015; Telzer, Miernicki, et al, 2018; van Hoorn, McCormick, Rogers, Ivory, & Telzer, 2018; Vorobyev et al, 2015), parents (Guassi Moreira & Telzer, 2018; Qu et al, 2016, 2015; Telzer, Ichien, et al, 2015; Telzer, Fuligni, et al, 2015; van Hoorn et al, 2018), and even siblings (Rogers, McCormick, van Hoorn, Ivory, & Telzer, 2018) influence adolescent neurodevelopment and risk taking (for a meta‐analysis, see van Hoorn, Shablack, Lindquist, & Telzer, 2019). These studies highlight a set of neural candidates to examine as promising indices of adolescent susceptibility to social influence.…”
mentioning
confidence: 99%
“…Sibling influence occurs above and beyond the effects of early child aggression, maternal mental health, marital status, family violence, parental criminality, and family income, suggesting that similarity in siblings’ risk-taking cannot be fully explained by shared experiences or genetics but is attributed to the sibling relationship itself (Slomkowski et al, 2005). Indeed, we found that adolescents’ perceptions of sibling closeness are associated with lower externalizing behavior via heightened AI activation when making safe decisions, an effect that persists above and beyond parental and peer closeness, highlighting the significant protective role of sibling relationships on adolescent externalizing behavior through the brain (Rogers et al, 2018). Interestingly, older siblings’ behavior influences adolescents’ decisions to engage in, or abstain from, risk taking, particularly among younger siblings who report they model their older sibling, and this is represented in the brain via shared neural patterns between younger and older siblings during risky decision-making in the VS, AI, and vmPFC (Rogers et al, 2021).…”
Section: Adolescents Do Not Orient Away From the Family But Continue ...mentioning
confidence: 87%
“…Participants played the YLG in the MRI scanner while alone, in presence of a peer and in the presence of a parent. In the current paper, we focused on the Peer presence and Parental presence conditions, because comparisons with an alone condition have been described in previous work (peer > alone, Chein et al ., 2011 ; parent > alone, Telzer et al ., 2015 ), and the alone condition is part of a separate manuscript focused on individual differences (Rogers et al ., 2018 ). Participants completed two runs for each social context condition, which were counterbalanced across participants.…”
Section: Methodsmentioning
confidence: 99%